Classical classification of divine rule (Hukum Shari'i): the denial off declaratory rule (Hukum Wada'i) - Abu Elgasim, Saad; Ansari, Abdul Haseeb; Arifin, Mahamad (INSI Publications, 2013)
Divine rule (Hukmshar‘i) has classically been classified into two kinds, namely, hukmtaklifi (defining rule) and hukmwad‘i (declaratory rule). This classical classification, despite having been the mainstream opinion in Islamic jurisprudence, has been challenged by a dissenting opinion to the effect that the independent existence of hukmwad‘i is denied. In other words, hukmtaklifihas been alleged to be the sole kind of which hukmwad‘i consists. This dissenting opinion in Islamic jurisprudence has been unsuccessful to the effect that it is hardly mentioned, and even when it is mentioned, it is mentioned in passing. This dissenting opinion, despite having been marginalized, is believed to be correct and, consequently, the main-stream opinion, despite having been established, is believed to be false. To justify such a daring submission, this paper takes it upon itself to revisit the classical classification of hukmshar‘i so as to prove the structural dependence of hukmwad‘i upon hukmtaklifi. To prove that, the paper will first present the subdivision of hukmwad‘i challenged in a fair manner so as to help the reader develop a clear and complete understanding of it. Subsequently, the subdivision presented will be scrutinized in an analytical manner so as to highlight the inevitable joints that connect hukmwad‘i to hukmtaklifi and, consequently, emphasize the structural dependence alleged. Having done so, we have arrived at the conclusion that the sole kind of which hukmshar‘i consists is hukmtaklifi. Hukmwad‘i, as a consequence, is an integral part of hukmtaklifi under which it is subsumed and to which it is subservient. In other words, hukmtaklifi and hukmwad‘i are structurally interlinked. Without hukmtaklifi, sense cannot be made of hukmwad‘i, and without hukmwad‘i, hukmtaklifi is incomplete.